THE EFFECT OF COMPANY DIVERSIFICATION TOWARDS EARNING MANAGEMENT MODERATED BY MANAGERIAL OWNERSHIP - Kusumaningtyas, Ratih; Yendrawati, Reni (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2015)
This study aims to examine the effect of diversification towards earnings management moderated by managerial ownership. The sample in this research is 48 manufacturing companies listed in Indonesian Stock Exchange period 2009- 2013. Purposive sampling was utilized as a sampling technique in this study. This research used moderating regression analysis to examine the proposed of hypothesis. The result found that diversification has significant positive effect on earnings management. Managerial ownership also has significant positive effect in moderating the relationship between corporate diversification with earnings management. While the three control variables such as company size (size), the companyâs growth (growth) and leverage have no significant effect on earnings management.